Effects of different basal media and complex addivtives interaction on in vitro seed germination and seedling growth of red kelmapayan (neolamarcka macrophylla) - Sew, Jun Wu (Universiti Malaysia Sarawak (UNIMAS), 2015)
Neolamarckia macrophylla (red kelampayan) is one of the fast growing tree species chosen for Sarawak planted forest project. Limited availability of red kelampayan seeds and low in situ germination percentage had restricted the local production of red kelampayan seedlings. To improve the conventional propagation method, this study had investigated the effects and interaction of complex additives to develop a low-cost protocol for in vitro propagation of N. macrophylla. Effects of three basal media (Murashige & Skoog, Gamborg B5 and half strength MS) on germination percentage of the red kelampayan seeds were investigated. The effects and interactions of B5 medium supplemented with the complex additives like the coconut water, CW 5, 10, 15 [%, (v/v)], the potato homogenate, PH 5, 10, 15 [%, (w/v)], and the banana homogenate, BH 5, 10, 15 [%, (w/v)]on in vitro seed germination and the seedling growth were studied. The parameters measured were seed germination percentage (%), number of leaves, plant height (mm), root length (mm) and number of roots. From this study, the B5 and MS media had the most significant germination percentage of 3.15% and 3.89%, respectively. The B5 medium supplemented with 15% BH had given the highest in vitro germination percentage of 5.73%. Whereas, the B5 medium supplemented with 10% CW had shown significant enhancement on the number of roots and leaves of the red kelampayan seedlings. The Duncan’s Multiple Range Test showed significant interaction between types and concentration of complex additives on in vitro seed germination and the seedling growth of the red kelampayan. Additionally, the developmental stages of N. macrophylla were studied to better understand the seed germination and the early growth of kelampayan. 120 g/L sago starch and 10% - 15% CW could potentially replace the costly conventional phyto-agarose and plant growth regulator, respectively. Under labscale, the inexpensive protocol established could potentially reduce the cost of culture medium per litre by 59%. The reduction of production cost will help to ensure a sustainable supply of kelampayan seedlings for planted forest development in Sarawak